A new hybid method for manufacturing sustainability performance assessment: a case study in furniture industry. Issue 1 (31st December 2022) - Utama, Dana Marsetiya; Ardiyanti, Nadiah; Putri, Anindya Apritha
ABSTRACT: Manufacturing sustainability performance evaluation is critical for improving the production line's performance. Three aspects involved in manufacturing sustainability are economic, social, and environmental. This research aims to create a new framework for assessing the Manufacturing Sustainability Score (MSS) based on the lean concept. A hybrid method involving the Delphi, Dematel-Analytical Network Process (ANP), Sustainability Value Stream Mapping (VSM), and Traffic Light System is proposed. The proposed framework is applied to a case study in the furniture industry, and the results demonstrate that the new framework can assess manufacturing sustainability performance. A case study's manufacturing sustainability score is 66.97 percent. It demonstrates that the company's performance is moderate and could be improved. The managerial and academic implications are also presented in this study.